Unsteady slip velocity to improve mass transfer in spiral wound reverse osmosis membrane (SWM) systems - Liang, Yong Yeow (2019)
An unsteady forced slip velocity has an important effect on the flow conditions adjacent to the membrane interface, which can help control concentration polarisation (CP) and fouling. This study explores the effect of non-sinusoidal slip velocity waveforms on mass transfer and shear stress in membrane channels. The main finding of this is that a non-sinusoidal waveform with a sudden decrease in slip velocity for systems without vortex shedding, can significantly increase maximum shear stress (>20%). The second objective of this work is to compare oscillating flow and slip velocity mass transfer enhancement in spacer-filled membrane channels. One of this finding is that the mechanism by which the flow perturbations are generated is not as important as the perturbation frequency, in terms of increasing wall shear and permeate flux. The third objective of this work is to investigate the effect of SWM feed spacer geometry on mass transfer enhancement driven by forced transient slip velocity. One of the finding of this is that the resonant frequency is significantly affected by the interaction of the shear layer with successive downstream spacers, hence affecting the degree of mass transfer effectiveness.